Assessment of public comments on the death of Queen Elizabeth II: A focus on twitter - Adams, Emmanuel Jibb; Hassan, Joan Tirwyn (Journal of Language, Literature, Social and Cultural Studies, 2024)
The study investigates public comments and reactions on the death of Queen Elizabeth II, focusing on the mixed responses generated on Twitter. The aim is to explore how the late monarch’s life, reign, and legacy are perceived and discussed, considering both truth and misinformation. Drawing from Agenda Setting and Framing theories, the research examines select public comments using hashtags like #QueenElizabethdead, #QueenElizabethII, and #QueenElizabeth. A mixed-method content analysis was employed, identifying themes based on attributes such as Type of Social Media, Source of Story, Frame of Story, and Tone of Story. The results reveal varying public sentiments, ranging from reverence to critique, highlighting polarized perspectives on the monarch’s legacy. These findings contribute to ongoing philosophical debates regarding the nature of truth, the portrayal of legacy, and the societal impact of prominent figures at death. The study concludes that the discourse surrounding Queen Elizabeth II’s death reflects deeper social tensions and provides insights into the role of framing and agenda-setting in shaping public opinion on prominent historical figures.